Bi particles with exposed (012) facet on 3D substrate as highly active and durable electrode for CO2 reduction to formate. (January 2022) - Wei, Xinying; Zhang, Weining; Liu, Depei; Liu, Duanduan; Yan, Yuandong; Zhang, Jie; Yang, Yandong; Yan, Shicheng; Zou, Zhigang
Graphical abstract: Highlights: Three-dimensional (3D) electrode are obtained with uniform and dense Bi nanoparticles. Bi nanoparticles with exposed (012) facet can improve selectivity for formate by stabilizing the OCHO* intermediate. The Bi NPs/CC electrode exhibited a Faraday efficiency of 97.4% for formate generation at -0.78 V vs. RHE. The Bi NPs/CC electrode exhibited a remarkable durability of 72 h without decay. Abstract: It is highly challenging to produce three-dimensional (3D) electrodes with the high activity, selectivity and durability for CO2 mediated energy conversion and storage devices. Here, we densely and uniformly dispersed Bi dendrites on 3D carbon cloth (CC) by controlling the coordinated strength between Bi ions and ligands and subsequently exposed (012) facet by reduction of chemically oxidized Bi dendrites to Bi nanoparticles (Bi NPs). As a result, the Bi NPs/CC electrode exhibited a current density of 6.8 mA cm −2 at -0.78 V vs. RHE with 97.4 % CO2 -to-formate Faradaic efficiency and remarkable durability of 72 h without decay. The theoretical calculations confirmed that the exposed specific facet to stabilize the OCHO* intermediate contributed to high activity, selectivity and durability of Bi NPs/CC electrode. Our results suggested a great potential to electrochemically construct 3D electrodes for large-scale applications in CO2 conversion.